Isotopic Structure of Lake Whitefish in Lake Huron: Evidence for Regional and Local Populations Based on Resource Use. (3rd January 2017) - Eberts, Rebecca L.; Wissel, Björn; Simpson, Gavin L.; Crawford, Stephen S.; Stott, Wendylee; Hanner, Robert H.; Manzon, Richard G.; Wilson, Joanna Y.; Boreham, Douglas R.; Somers, Christopher M.
Abstract: Lake Whitefish Coregonus clupeaformis is the most commercially valuable species in Lake Huron. The fishery for this species has historically been managed based on 25 management units (17 in Canada, 8 in the USA). However, congruence between the contemporary population structure of Lake Whitefish and management units is poorly understood. We used stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N), food web markers that reflect patterns in resource use (i.e., prey, location, habitat), to assess the population structure of spawning‐phase Lake Whitefish collected from 32 sites (1, 474 fish) across Lake Huron. We found large isotopic variation among fish from different sites (ranges: δ 13 C = 10.2‰, δ 15 N = 5.5‰) and variable niche size and levels of overlap (standard ellipse area = 1.0–4.3‰ 2 ). Lake Huron contained spawning‐phase fish from four major isotopic clusters largely defined by extensive variation in δ 13 C, and the isotopic composition of fish sampled was spatially structured both within and between lake basins. Based on cluster compositions, we identified six putative regional groups, some of which represented sites of high diversity (three to four clusters) and others with less (one to two clusters). Analysis of isotopic values from Lake Whitefish collected from summer feeding locations and baseline prey items showed similar isotopic variation and established spatial linkage between spawning‐phase and summer fish. Our results show that summer feeding location contributes strongly to the isotopic structure we observed in spawning‐phase fish. One of the regional groups we identified in northern Georgian Bay is highly distinct based on isotopic composition and possibly ecologically unique within Lake Huron. Our findings are congruent with several previous studies using different markers (genetics, mark–recapture), and we conclude that current management units are generally too small and numerous to reflect the population structure of Lake Whitefish in Lake Huron. Received June 2, 2016; accepted October 3, 2016Published online January 3, 2017